Temporal transcriptome and metabolite analyses provide insights into the biochemical and physiological processes underlying endodormancy release in pistachio (Pistacia vera L.) flower buds - Yu, Shu; Amaral, Douglas; Brown, Patrick H.; Ferguson, Louise; Tian, Li (Frontiers in Plant Science, 2023)
Pistachio (Pistacia vera L.), an economically and nutritionally important tree crop, relies on winter chill for bud endodormancy break and subsequent blooming and nut production. However, insufficient winter chill poses an increasing challenge in pistachio growing regions. To gain a better understanding of the physiological and biochemical responses of endodormant pistachio buds to chilling accumulation, we investigated the global gene expression changes in flower buds of pistachio cv. Kerman that were cultivated at three different orchard locations and exposed to increasing durations of winter chill. The expression of genes encoding β-1,3-glucanase and β-amylase, enzymes responsible for breaking down callose (β-1,3-glucan) and starch (α-1,4-glucan), respectively, increased during the endodormancy break of pistachio buds. This result suggested that the breakdown of callose obstructing stomata as well as the release of glucose from starch enables symplasmic trafficking and provides energy for bud endodormancy break and growth. Interestingly, as chilling accumulation increased, there was a decrease in the expression of nine-cis-epoxycarotenoid dioxygenase (NCED), encoding an enzyme that uses carotenoids as substrates and catalyzes the rate-limiting step in abscisic acid (ABA) biosynthesis. The decrease in NCED expression suggests ABA biosynthesis is suppressed, thus reducing inhibition of endodormancy break. The higher levels of carotenoid precursors and a decrease in ABA content in buds undergoing endodormancy break supports this suggestion. Collectively, the temporal transcriptome and biochemical analyses revealed that the degradation of structural (callose) and non-structural (starch) carbohydrates, along with the attenuation of ABA biosynthesis, are critical processes driving endodormancy break in pistachio buds.